PREVALENCIJA SINDROMA NISKE PREDNJE RESEKCIJE KOD BOLESNIKA SA KARCINOMOM REKTUMA KOJI SU BILI PODVRGNUTI HIRURŠKOM LEČENJU U GRADSKOJ BOLNICI ISFAHAN TOKOM 2012-2018 - Sanei, Behnam; Ghasemi Fard, Mohammad; Kolahduzan, Mohsen (Medicinski časopis, 2020)
Objective. We aimed to determine the relative frequency of low anterior resection syndrome (LARS) in patients with rectal cancers who underwent surgical treatment in Isfahan.Methods. We evaluated all patients who referred to the surgery clinic of Saint Al-Zahra hospital in Isfahan within six years. After identifications, if LARS, according to the LARS score tool, the frequency of resection complications, factors affecting the LARS, morbidity, and mortality, the frequency distribution of defecation, stool consistency, and rate of significant improvement was evaluated.Results. Fifty-two patients were evaluated. The prevalence of LARS was 78.8%. Postoperative fecal and gas incontinence, clustering, fecal frequency, and fecal urgency in LARS patients were significantly higher than patients without LARS (P